Urban child and adolescent mental health services : a responsive approach to communities - Afuape, Taiwo, 1975-; Krause, Inga-Britt (London ; New York : Routledge, Taylor & Francis Group, 2016)
Urban Child and Adolescent Mental Health Services weaves together different strands of mental health work undertaken in one inner-city Child and Adolescent Mental Health Service by professionals working in a range of ways. In particular, it provides examples of how an urban CAMH service has been responsive to, and influenced by, local circumstances, resources and knowledge. The book explores the relationship between professionals and the community context, which provides the background to the lives of individual service users and the families they serve, and how this relationship is integral to the development of a responsive service. The chapters cover a range of settings and approaches, addressing the social, cultural, political and community contexts impacting on children, young people and families. In this way Urban Child and Adolescent Mental Health Services explores challenges and issues emerging in a responsive approach to child and family work in all community settings whether they be urban, suburban or rural. Urban Child and Adolescent Mental Health Services is intended for mental health and social care professionals involved in therapeutic, social and pastoral work with children, young people, families and communities. The book will be of interest to policy-makers, mental health and social care professionals, health visitors, general practitioners, nurses and midwives, as well as to trainees in these professions including trainee clinical psychologists, social workers or psychoanalytic and systemic psychotherapists. It will also appeal to those interested in responsive communities and critical approaches to therapeutic interventions in mental health work, psychology, psychotherapy and counselling.
Includes bibliographical references and index.
Keywords: Mental health services -- Great Britain; Community mental health services -- Great Britain; Child mental health services -- Great Britain; Minorities -- Mental health services -- Great Britain; Adolescent psychiatry -- Great Britain; Urban youth -- Great Britain